Tracking the evolution of hospice palliative care in Canada: A comparative case study analysis of seven provinces - Richards Judy-Lynn; Kelley Mary-Lou; Whitfield Kyle; Crooks Valorie A; Williams Allison M; DeMiglio Lily; Dykeman Sarah (BMC, 2010)
Abstract Background An aging population, rise in chronic illnesses, increase in life expectancy and shift towards care being provided at the community level are trends that are collectively creating an urgency to advance hospice palliative care (HPC) planning and provision in Canada. The purpose of this study was to analyze the evolution of HPC in seven provinces in Canada so as to inform such planning and provision elsewhere. We have endeavoured to undertake this research out of awareness that good future planning for health and social care, such as HPC, typically requires us to first look backwards before moving forward. Methods To identify key policy and practice events in HPC in Canada, as well as describe facilitators of and barriers to progress, a qualitative comparative case study design was used. Specifically, the evolution and development of HCP in 7 strategically selected provinces is compared. After choosing the case study provinces, the grey literature was searched to create a preliminary timeline for each that described the evolution of HPC beginning in 1970. Key informants (n = 42) were then interviewed to verify the content of each provincial timeline and to discuss barriers and facilitators to the development of HPC. Upon completion of the primary data collection, a face-to-face meeting of the research team was then held so as to conduct a comparative study analysis that focused on provincial commonalities and differences. Results Findings point to the fact that HPC continues to remain at the margins of the health care system. The development of HPC has encountered structural inheritances that have both sped up progress as well as slowed it down. These structural inheritances are: (1) foundational health policies (e.g., the Canada Health Act); (2) service structures and planning (e.g., the dominance of urban-focused initiatives); and (3) health system decisions (e.g., regionalization). As a response to these inheritances, circumventions of the established system of care were taken, often out of necessity. Three kinds of circumventions were identified from the data: (1) interventions to shift the system (e.g., the role of advocacy); (2) service innovations (e.g., educational initiatives); and (3) new alternative structures (e.g., the establishment of independent hospice organizations). Overall, the evolution of HPC across the case study provinces has been markedly slow, but steady and continuous. Conclusions HPC in Canada remains at the margins of the health care system. Its integration into the primary health care system may ensure dedicated and ongoing funding, enhanced access, quality and service responsiveness. Though demographics are expected to influence HPC demand in Canada, our study confirms that concerned citizens, advocacy organizations and local champions will continue to be the agents of change that make the necessary and lasting impacts on HPC in Canada.